The moderating effect of self-efficacy on supervisory support and organizational citizenship behavior - Abdullah, Meor Rashydan; Wider, Walton (Frontiers in Psychology, 2022)
The study aims to examine the moderating effect of self-efficacy on supervisory support and organisational citizenship behaviour (OCB). An individual's self-efficacy is defined as their belief in their own ability to successfully complete a goal or task, which influences their motivation, persistence, and decision-making. This study is based on the Conservation of Resource Theory, which holds that personal resources such as self-efficacy can influence employees' perceived support and extra-role behaviour (OCB). The data were collected from 618 employees in four public sector organisations in Putrajaya, Malaysia through a questionnaire survey and analysed using the partial least squares structural equation modelling (PLS-SEM) technique. Resultantly, supervisory support demonstrated a significant positive relationship with OCB. The results suggested that personal resources, such as self-efficacy increase the level of OCB with lower or higher perceived supervisory support. The results highlighted that self-efficacy strengthens supervisory support relations with OCB when supported by employees’ self-belief and confidence. It is critical to investigate the role of self-efficacy because industries must constantly change, and employees must have self-efficacy resources to continuously improve and sustain their performance level. The findings can contribute to the literature and open new avenues for future research.